Influence of rest on mechanical properties of GaP single crystals deformed by scleroscopic method at different temperatures - Jitaru, Raisa (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2008)
The areas of the GaP (111) plane placed between the scratches parallel to [110] have